2009
DOI: 10.1158/1535-7163.mct-08-0592
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 modulates biological functions of pancreatic cancer cells including their proliferation, invasion, and chemoresistance

Abstract: Due to the poor prognosis of pancreatic cancer, novel diagnostic modalities for early diagnosis and new therapeutic strategy are urgently needed. Recently, microRNA-21 (miR-21) was reported to be strongly overexpressed in pancreatic cancer as well as in other solid cancers. We investigated the functional roles of miR-21, which have not been fully elucidated in pancreatic cancer. miR-21 expression was assessed in pancreatic cancer cell lines (14 cancer cell lines, primary cultures of normal pancreatic epithelia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
241
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(251 citation statements)
references
References 35 publications
9
241
0
1
Order By: Relevance
“…In line with this assumption, pancreatic cancer cells transfected with the miR-21 precursor show significantly increased cell proliferation, invasiveness, and chemoresistance. 17 It is notable that a high miR-21 expression was associated with a poorer prognosis of the pancreatic ductal adenocarcinoma patients in the current study, and the association has also been described by Dillhoff et al 18 Moreover, the expression status of miR-21 was considered to be an independent prognostic factor for poor survival based on our statistical analysis. Zhu et al 19 described that miR-21 has a role not only in tumor growth, but also in invasion and tumor metastasis using several cancer cell lines.…”
Section: Discussionsupporting
confidence: 84%
“…In line with this assumption, pancreatic cancer cells transfected with the miR-21 precursor show significantly increased cell proliferation, invasiveness, and chemoresistance. 17 It is notable that a high miR-21 expression was associated with a poorer prognosis of the pancreatic ductal adenocarcinoma patients in the current study, and the association has also been described by Dillhoff et al 18 Moreover, the expression status of miR-21 was considered to be an independent prognostic factor for poor survival based on our statistical analysis. Zhu et al 19 described that miR-21 has a role not only in tumor growth, but also in invasion and tumor metastasis using several cancer cell lines.…”
Section: Discussionsupporting
confidence: 84%
“…For example, miR-122a is down-regulated in 70% of HCCs (14) and its ectopic expression can significantly increase the sensitivity to doxorubicin and sorafenib in HCC cells (15,16). miR-21 is up-regulated in many cancers and contributes to the chemoresistance to gemcitabine in cholangiocarcinoma and pancreatic cancer cells (17)(18)(19). Members of the let-7 family of miRNAs are downregulated in human HCC cells and tissues in association with enhanced expression of Bcl-xL, and ectopic expression of let-7c miRNA sensitizes HCC cells to sorafenib (20).…”
Section: Technology In Cancer Research and Treatment Volume 13 Numbermentioning
confidence: 99%
“…However, a recent report showed that miR-369-3p can upregulate the expression of tumor necrosis factor alpha (Vasudevanet al, 2007). In addition, miRNAs have been shown to function as tumor suppressors or oncogenes (Bracken et al, 2009;Esquela-Kerscher et al, 2006;Huang et al, 2008;Kumar et al, 2007;Lee et al, 2007;Liu et al, 2009;Moriyama et al, 2009;Ryan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%